O Dragão do Mar na Terra da Luz: a construção do herói jangadeiro (1934-1958) - Xavier, Patrícia Pereira (2010)
Ceará was the first province to free its captives in 1884, four years before the Lei Áurea (Abolicionist law), for this reason it received the epithet of Land of the light . Francisco José do Nascimento, known as Dragon of the sea , entered the written history of Ceará as the fisherman who would have lead his fellowmen in 1881, so that his rafts would not transport the slaves that would be sent to the farms in the south, in the episode that became konwn as the fishermen s strike. The goal of this study is to understand how the memory of Dragão do Mar was built, between the period of the celebrations of fifty years of abolition in 1934 until the release of the book A hero without a pedestal by Roberto Átila do Amaral Vieira, published in 1958